The case of high motivation and low achievement in science: what is the role of students' epistemic beliefs?. Issue 11 (24th July 2019) - Karakolidis, Anastasios; Pitsia, Vasiliki; Emvalotis, Anastassios
ABSTRACT: The importance of motivation-related factors in shaping students' academic achievement across a range of areas, including science, has been consistently acknowledged by the existing research literature. In an effort to improve students' science achievement, many education systems put particular emphasis on the enhancement of intrinsic (i.e. enjoyment and interest) and instrumental motivation in the subject. However, based on the latest Programme for International Student Assessment (PISA) data, many of the countries that managed to increase their motivation indices between 2006 and 2015 did not necessarily note a rise in science performance, with many still performing below the Organisation for Economic Co-operation and Development (OECD) average. Interestingly, although students' motivation increased in some of these countries (e.g. Luxembourg, Iceland and Greece), their average performance in science decreased. Using the PISA 2015 data for Greece, this study examined the case of high motivation and low achievement in science by incorporating epistemic beliefs in the discussion. The multilevel analysis confirmed the importance of 15-year-old students' motivation for learning science in predicting their science achievement and highlighted the positive predictive power of their epistemic beliefs. Policy and practice recommendations are provided based on the study findings, stressing the key role of students' epistemic beliefs.